1983
DOI: 10.1524/ract.1983.32.13.105
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer Spectroscopy in Actinide Research

Abstract: Actinide compounds /Mössbauer spectroscopy /Electronic structure /Crystal structure /Magnetism L Introduction Π. Information accessible to Mössbauer spectroscopy ΙΠ. Mössbauer spectroscopy in the actinide elements 1. Introduction 2. Reported resonances 3. Other possibilities IV.Electionic configuration, bonding and magnetic properties 1. Introductory survey of theoretical concepts 2. Chemical information from isomer shift data 3. Chemical information from electric field gradient data 4. Chemical information fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…A substantial number of complex oxides of Np(VII) have been prepared, but attempts at fluorides or oxyfluorides have not succeeded [18]. A powerful tool for study of neptunium chemistry -especially appropriate in view of its multiplicity of oxidation states -is Mössbauer spectroscopy, for which the isomer shifts of the metal, intermetallic Compounds, and many Np(III) through Np(VII) Compounds show clearly the tetravalent nature of the metal and the degrees of ionic/covalent behavior of its Compounds [19,20].…”
Section: Neptuniummentioning
confidence: 99%
“…A substantial number of complex oxides of Np(VII) have been prepared, but attempts at fluorides or oxyfluorides have not succeeded [18]. A powerful tool for study of neptunium chemistry -especially appropriate in view of its multiplicity of oxidation states -is Mössbauer spectroscopy, for which the isomer shifts of the metal, intermetallic Compounds, and many Np(III) through Np(VII) Compounds show clearly the tetravalent nature of the metal and the degrees of ionic/covalent behavior of its Compounds [19,20].…”
Section: Neptuniummentioning
confidence: 99%
“…Finally, looking at general trends among heptavalent neptunium compounds, Friedt et al reported an increasing linear variation of the quadrupole coupling constant as a function of isomer shift 30,37 through the series of compounds Li 5 NpO 6 , Cs 3 NpO 5 , Rb 3 NpO 5 , CsNpO 4 , and RbNpO 4 , which was related to the increasing occupation of the 5f and 6d atomic orbitals. The parameters reported by Jovéet al for Ba 2 NaNpO 6 and K 3 NpO 5 , 24 and those found herein for the Na 5 NpO 6 compound, fit this trend very well as shown in Figure 7.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
“…Concerning the actinide elements, reviews have been reported by Friedt (90) and by Potzel et al (255). A review of 197Au Mossbauer spectroscopy is given by Parish (244).…”
Section: Chemical Studies (Other Isotopes)mentioning
confidence: 99%